Death by a Thousand Cuts: Recognizing, Reporting, and Responding to Corruption in Local Government. (2nd January 2020) - Yates, Allan; Graycar, Adam
Abstract : Corruption is perceived to exist in local government in Australia. This article explores the disparity between reports of perceived corruption by the public and reports by councils. It notes that perceived corruption in local government is not always recognized by local government officials; when it is, it is often not reported, or if it is reported, it does not receive an adequate response. Research undertaken with 251 employees in 10 Australian Councils raises issues of whether the corruption is systemic, or a set of isolated transgressions. If transgressions are not addressed, they risk becoming normalized, resulting in systemic corruption, and an ethical demise—a death by a thousand cuts.